Mapping QTLs for early leaf spot resistance and yield component traits using an interspecific AB-QTL population in peanut - Gomis, J.; Sambou, A.; Nguepjop, J. R.; Tossim, H. A.; Seye, M.; Djiboune, R.; Sambakhe, D.; Loko, D.; Conde, S.; Alyr, M. H.; Bertioli, D. J.; Leal-Bertioli, S. C. M.; et al. (Frontiers in Plant Science, 2025)
Early leaf spot (ELS), caused by Passalora personata (syn. Cercospora arachidicola), is a highly damaging peanut disease worldwide. While there are limited sources of resistance in cultivated peanut cultivars, wild relatives carry alleles for strong resistance, making them a valuable strategic resource for peanut improvement. So far, only a few wild diploid species have been utilized to transfer resistant alleles to cultivars. To mitigate the risk of resistance breakdown by pathogens, it is important to diversify the sources of resistance when breeding for disease resistance. In this study, we created an AB-QTL population by crossing an induced allotetraploid (IpaCor1), which combines the genomes of the diploid species Arachis ipaënsis and A. correntina, with the susceptible cultivar Fleur11. A. correntina has been reported to possess strong resistance to leaf spot diseases. The AB-QTL population was genotyped with the Axiom-Arachis 48K SNPs and evaluated for ELS resistance under natural infestation over three years in Senegal. Marker/trait associations enabled the mapping of five QTLs for ELS resistance on chromosomes A02, A03, A08, B04, and B09. Except for the QTL on chromosome B09, the wild species contributed favorable alleles at all other QTLs. One genomic region on chromosome A02 contained several relevant QTLs, contributing to ELS resistance, earliness, and increased biomass yield, potentially allowing marker-assisted selection to introduce this region into elite cultivars. This study's findings have aided in diversifying the sources of resistance to ELS disease and other important agronomic traits, providing another compelling example of the value of peanut wild species in improving cultivated peanut.